IMPACT OF INDONESIA – ALGERIA COOPERATION IN INDUSTRIAL SECTOR CASE STUDY: WOODEN FURNITURE INDUSTRY EXPORTS FROM 2014-2016 - Nurkamila, Siti; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to explain the impact of cooperation by the Indonesian wooden furniture industry exports to the Algeria in 2014-2016. Algeria has routinely imported wooden furniture from Malaysia to supply their needs in domestic furniture. In fact, Algerian entrepeneurs know furniture from Malaysia mostly come from Indonesia. One of the factors because there is no agreement from Indonesia and Algeria to cooperate in the industrial sector especially the furniture industry sector.The theories used in this research is interdependence theory and comparative advantage thery. The author used liberalism approach. Data of this research was obtained from books, journals, articles, official document and websites that support the hyphotesis.The result of this study indicate that after the agreement, the dollar exchange rate at that time also affected the amount of wooden furniture exports. If the dollar is more expensive, then the interest of furniture buyers come down because of the buyers want the same price as before the dollar increase. Apart from the amount of wooden furniture exports, the number of workers and the number of furniture industrial also affected.Keywords: Wooden Furniture, Exports, Dollar Exchange